Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
663179
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti